2005
DOI: 10.3354/meps304133
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of lipids during early development of the sea urchin Evechinus chloroticus

Abstract: Detailed studies of lipid utilization during bivalve development have shown that lipids are important at 2 critical periods: embryogenesis and metamorphosis. Using the Iatroscan TLC/FID system I examined lipid class utilization during development of Evechinus chloroticus to determine whether lipids were also important for an echinoderm at these times. Eggs of E. chloroticus contained 34.41 ng of lipid, primarily polar lipids (52.0%) and triglyceride (29.4%). To determine whether there was a different pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 48 publications
3
120
0
1
Order By: Relevance
“…They suggested that this is probably due to the presence, at stage 4, immediately before the release of gametes, of high levels of gametes with diVerent fatty acid composition. Triglycerides, important for embryos during early development, are the main non-polar lipids in the eggs of sea urchins (Kozhina et al 1978;Sewell 2005;Villinski et al 2002;Yasumasu et al 1984) but are present at very low levels or even absent in spermatozoa where phospholipids clearly predominate (Kozhina et al 1978;Mita et al 1994). Triglycerides and phospholipids have usually distinctive fatty acid proWles and, for example, in the gametes of diVerent sea urchin species, it has been shown that phospholipids have higher levels of 18:0, 20:4n-6 and 20:5n-3 than triglycerides but lower proportions of 14:0, 16:0 and 16:1n-7 (Kozhina et al 1978;Metzman et al 1978;Mita et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that this is probably due to the presence, at stage 4, immediately before the release of gametes, of high levels of gametes with diVerent fatty acid composition. Triglycerides, important for embryos during early development, are the main non-polar lipids in the eggs of sea urchins (Kozhina et al 1978;Sewell 2005;Villinski et al 2002;Yasumasu et al 1984) but are present at very low levels or even absent in spermatozoa where phospholipids clearly predominate (Kozhina et al 1978;Mita et al 1994). Triglycerides and phospholipids have usually distinctive fatty acid proWles and, for example, in the gametes of diVerent sea urchin species, it has been shown that phospholipids have higher levels of 18:0, 20:4n-6 and 20:5n-3 than triglycerides but lower proportions of 14:0, 16:0 and 16:1n-7 (Kozhina et al 1978;Metzman et al 1978;Mita et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…During gametogenesis, they can be used as a source of energy (Marsh and Watts 2001) and, additionally, sea urchin spermatozoa obtain energy for swimming through oxidation of fatty acids derived either from phosphatidylcholine or from triglycerides (Mita and Nakamura 2001). In the eggs, triglycerides are important for larval development and survival (Kozhina et al 1978;Sewell 2005;Yasumasu et al 1984). Sea urchins as many other marine animals are able to synthesize most fatty acids but dietary lipids also provide the essential fatty acids linoleic (18:2n-6) and -linolenic (18:3n-3) and some other important long-chain n-6 and n-3 polyunsaturated fatty acids such as arachidonic (20:4n-6) and eicosapentaenoic (20:5n-3) acids.…”
Section: Introductionmentioning
confidence: 99%
“…The higher concentration of FFA, DG and AMPL in moribund larvae may reflect TAG and PL catabolism. Indeed, FFA, DG and monoacylglycerides (included in the AMPL) usually result from TAG and PL degradation by lipase (Derewenda 1994;Sewell 2005). …”
Section: Characterization Of the Massive Mortalitymentioning
confidence: 99%
“…data). It has long been recognized that neutral lipids, particularly triglycerides, are an important energy source that fuels the early larval development of planktotrophic echinoids and the embryogenesis and metamorphosis of mollusks (reviewed by Sewell 2005). The possibility of sizedependent allocation of energy reserves in hatchlings, and consequences for performance, is the subject of ongoing studies.…”
Section: Size-dependent Performance Of Juveniles Under Starvationmentioning
confidence: 99%